Digital Transformation in Accounting: Challenges, Risks, and Financial Reporting Quality - Waad Dhahir Oleiwi (Studi Akuntansi dan Bisnis Indonesia, 2026)
The accounting profession is undergoing radical transformations as a result of the digital technological revolution sweeping the world. This study aims to analyze the challenges and risks arising from digital transformation in the accounting profession and its impact on the reliability of financial statements and the quality of accounting reports. The study employs a descriptive analytical approach to explore the dimensions of these transformations and their various effects. The results indicate that digital transformation presents tremendous opportunities to improve the efficiency of accounting processes and increase the accuracy of reports. However, it also poses new challenges related to information security, data protection, and the need for retraining accounting personnel. The study also emphasizes the necessity of establishing a robust regulatory framework to ensure the optimal utilization of digital technology while maintaining the reliability of accounting information and the quality of financial reports.